What Services, or Work Units, Do Nurses Experience in a More Traumatic Way When Entering the Professional World in Tenerife, Spain? A Phenomenological Study (Journal of Organizational Psychology, 2021)
The aim of this research is to investigate in which units or services the incorporation of nurses in Tenerife (Spain), is lived in a more difficult or traumatic way. In order to do so, a phenomenological hermeneutic investigation was carried out, by conducting an anonymous and confidential interview with nurses who have worked in public or private health institutions on the island of Tenerife and who have graduated from the University of La Laguna between 2009 and 2014. Three categories of the results of the interview data collection are established: ICU, OR and pediatrics. The incorporation to these services is often done in a hasty manner, without previous preparation of the nurses in these services. The participants in this study state they need support and better integration in these complex units.
Keywords: organizational psychology; novice nurse; job incorporation; stress; phenomenology